2007
DOI: 10.1111/j.1439-0434.2007.01292.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Cryphonectria hypovirus 1 in China, Japan and Italy

Abstract: The aim of this study was to examine the origin of Cryphonectria hypovirus 1 (CHV1) which infects chestnut blight fungus, Cryphonectria parasitica. The genetic diversity of 39 CHV1 isolates from China, Japan and Italy was assessed by combining sequencing and restriction fragment length polymorphic (RFLP) experiments. Based on their partial sequences, 26 CHV1 isolates within 26 haplotypes were grouped into three subtypes. The 17 viruses from China were distributed between subtypes I and III, while all four of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
(54 reference statements)
3
6
0
Order By: Relevance
“…These results are in agreement with a genetic analysis of ORF A with CHV1 strains, showing that Italian strains might have originated in Japan (Liu et al. ). All these data suggest that the viral A3‐B3 lineage followed its host lineage G1 from Japan to Europe.…”
Section: Discussionsupporting
confidence: 92%
“…These results are in agreement with a genetic analysis of ORF A with CHV1 strains, showing that Italian strains might have originated in Japan (Liu et al. ). All these data suggest that the viral A3‐B3 lineage followed its host lineage G1 from Japan to Europe.…”
Section: Discussionsupporting
confidence: 92%
“…Previous analyses (Liu et al. ) of Asian and European CHV‐1 discovered that the genetic diversity among Asian isolates was higher than among European isolates, indicating that the European CHV‐1 populations had emerged more recently. The four European subtypes of CHV‐1 (I, F1, F2, and D) were more closely related to each other than to any of the Asian isolates.…”
Section: Discussionmentioning
confidence: 97%
“…Since CHV‐1 has been found in China and Japan, it has been assumed that CHV‐1 was introduced together with C. parasitica from Asia (Liu et al. ). Records of first detection of hypovirulent C. parasitica in different regions indicated that CHV‐1 spread throughout Europe following the spread of the fungus with a lag in time (Heiniger and Rigling ; Robin and Heiniger ).…”
Section: Introductionmentioning
confidence: 99%
“…dsRNA profiles can be quite diverse even within isolates of the same fungus. In some cases they show geographical structuring (Liu et al ., 2007a,b; Park et al ., 2006a,b; Voth et al ., 2006) but often they do not (Howitt et al ., 1995; Rong et al ., 2001; Tsai et al ., 2004). Tsai et al .…”
Section: Diversity and Incidence Of Mycovirusesmentioning
confidence: 99%